A high-strength PP plastic and preparation method
By loading the modified nanosilica onto the polyphenylene sulfide fiber in PP plastic and combining it with other components to form a crosslinked structure, the problem of insufficient strength of traditional PP plastics is solved, and the strength and toughness of the material are significantly improved.
Patent Information
- Application Number
- CN202411200887.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-08-29
AI Technical Summary
Traditional PP plastics have shortcomings in strength, which leads to being fragile when subjected to external forces, limiting their application scope.
By loading the modified nanosilica onto polyphenylene sulfide fibers and combining them with components such as γ-chloropropyltrimethoxysilane, maleic anhydride grafted polypropylene resin, a crosslinked structure is formed to enhance interfacial compatibility and stress transfer efficiency.
It significantly improves the strength and toughness of the material, optimizes the overall performance of the material, and avoids premature material damage caused by stress concentration.
Smart Images

Figure BDA0005017812320000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polypropylene materials and relates to a high-strength PP plastic and a preparation method thereof. Background Art
[0002] With the continuous development of social economy and the continuous improvement of people's living standards, daily plastic products play an increasingly important role in people's daily lives. Whether in household goods, office supplies or various industrial products, plastic products can be seen. As a common plastic material, PP plastic is widely used in various fields of daily life because of its good chemical stability, insulation and relatively low cost. For example, fresh-keeping boxes, storage boxes, storage racks, pet utensils, etc., provide people with various conveniences.
[0003] However, the strength defects of traditional PP plastics have gradually become apparent in actual use. From the perspective of raw materials, the molecular chain structure of PP plastics is relatively regular, which makes it have a high degree of crystallinity. When subjected to external forces, stress concentration is easily generated at the interface between the crystalline region and the amorphous region, resulting in embrittlement of the material and insufficient strength. In addition, the macromolecular chain of PP plastics is not flexible enough, lacking sufficient ductility and toughness, and often appears fragile when subjected to large external impacts. This lack of strength has greatly limited the application of PP plastics.
[0004] In order to make up for the shortcomings of PP plastic in terms of strength and improve its performance to adapt to a wider range of application scenarios, various reinforcing materials and additives are usually tried at this stage. However, this treatment still has shortcomings in application. For example, the compatibility between the reinforcing material and the PP matrix is poor, which makes it difficult for the two to be closely combined and the role of the reinforcing material cannot be fully exerted, or the strength of the material is enhanced alone, while the synergy with other properties is ignored, which limits the improvement of the overall performance of the plastic. In view of this, the improvement process of the strength of PP materials is still a major research direction at present. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength PP plastic and a preparation method thereof. The present invention loads modified nano-silica on polyphenylene sulfide fibers, and cooperates with components such as γ-chloropropyltrimethoxysilane and maleic anhydride grafted polypropylene resin to jointly improve the performance of polypropylene materials. Through chemical bonding and physical entanglement, the cross-linking structure between molecular chains is enhanced, thereby enhancing the interface compatibility and stress transfer efficiency, significantly improving the strength of the material, and optimizing the overall performance of the material.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing high-strength PP plastic, the preparation method comprising the following steps:
[0008] (1) mixing polyphenylene sulfide and N-methyl pyrrolidone, and stirring at room temperature for 8-12 hours to obtain a polyphenylene sulfide solution;
[0009] (2) After stirring the modified nano-silica and N-methylpyrrolidone for 1-2 hours, the modified nano-silica and N-methylpyrrolidone are added dropwise to the polyphenylene sulfide solution and stirred at variable speed to obtain a mixed solution;
[0010] (3) electrospinning the mixed solution, and drying it in vacuum at 70° C. for 10 h after spinning to obtain polyphenylene sulfide fibers loaded with modified nano-silica;
[0011] (4) Polypropylene, polyphenylene sulfide fiber loaded with modified nano-silica, calcium stearate, γ-chloropropyltrimethoxysilane, maleic anhydride grafted polypropylene resin and potassium persulfate are mixed, stirred at 50-70° C. for 2-3 hours, melted in a twin-screw extruder, extruded and annealed to obtain a high-strength PP plastic.
[0012] Furthermore, in step (1), the mass ratio of the polyphenylene sulfide to N-methylpyrrolidone is 0.8-1.2:15-25.
[0013] Furthermore, in step (2), the mass ratio of the modified nano-silica, N-methylpyrrolidone and polyphenylene sulfide solution is 1.39-1.73:8-12:20-30;
[0014] The preparation method of the modified nano silicon dioxide is:
[0015] Nano-silica with an average particle size of 30-70 nm, anhydrous ethanol, methyltriethoxysilane, polyethylene glycol with a molecular weight of 2000 and potassium persulfate are ultrasonically mixed in a mass ratio of 1.1-2.5:15-25:0.08-0.12:0.15-0.25:0.01-0.03, stirred at 60-100° C. for 3-5 hours, centrifuged, filtered through a 200-mesh filter cloth, and the resulting precipitate is washed with anhydrous ethanol and dried at 60° C. for 12 hours to obtain modified nano-silica.
[0016] Furthermore, the parameters of the ultrasonic step are: ultrasonic frequency of 30-50kHz, ultrasonic temperature of 40-60°C, and ultrasonic time of 20-40min; the parameters of the centrifugal step are: centrifugal speed of 6000-10000rmp, and centrifugal time of 10-20min.
[0017] Furthermore, the flow rate of the dropwise addition step in step (2) is 5 mL / min; the parameters of the variable speed stirring are: the stirring temperature is 70-90°C, first stirring at a speed of 400-600 rpm for 1-3 hours, and then stirring at a speed of 1200-1800 rpm for 20-40 minutes.
[0018] Furthermore, the parameters of the electrospinning step in step (3) are: voltage of 12-20 kV, distance between the nozzle and the receiving plate of 12-18 cm, flow rate of 0.3-0.7 mL / h, and stretching ratio of 8-12.
[0019] Furthermore, in step (4), the mass ratio of the polypropylene, the polyphenylene sulfide fiber loaded with modified nano-silica, the calcium stearate, the γ-chloropropyltrimethoxysilane, the maleic anhydride grafted polypropylene resin and the potassium persulfate is 5.2-7:1.12-1.3:0.28-0.46:0.3-0.7:0.6-1:0.02-0.04.
[0020] Furthermore, the parameters of the twin-screw extruder in step (4) are: extrusion temperature of 100-140°C, extrusion pressure of 14-18MPa, and extrusion speed of 25-35m / min; the parameters of the annealing step are: annealing temperature of 100-110°C, and annealing time of 1.3-1.5h.
[0021] Beneficial effects of the present invention:
[0022] (1) The polyphenylene sulfide of the present invention contains benzene rings and sulfide bonds, which give it high rigidity and strength. When mixed with N-methylpyrrolidone, the solvent molecules enter the gaps between the molecular chains, destroying some of the intermolecular forces, allowing the polyphenylene sulfide molecular chains to stretch and expose more active sites. Therefore, when interacting with other components in the subsequent process, the polyphenylene sulfide can be more evenly combined to form a tighter structure, thereby improving the overall performance of the material. During the modification process, the hydrolysis reaction of methyltriethoxysilane causes it to condense with the hydroxyl groups on the surface of nano-silica, thereby introducing hydrophobic methyl groups into the surface. When it comes into contact with polymers such as polyphenylene sulfide, due to the similarity with the polymer molecular chains, it can better interpenetrate and fuse with each other, significantly reducing the interfacial tension between the two phases; on this basis, the flexible long chains introduced by polyethylene glycol increase the movable part in the molecular structure, absorbing and dispersing the stress when the material is subjected to external force; in addition, these flexible long chains may form a complex network structure with the polyphenylene sulfide molecules through physical entanglement, thereby enhancing the binding force between the polyphenylene sulfide molecules and limiting the free slip and movement of the molecular chains. The polyphenylene sulfide fibers loaded with modified nano-silica can effectively improve the strength and toughness of the material and avoid premature damage to the material due to stress concentration.
[0023] (2) The polypropylene molecular chain in the present invention has certain flexibility and crystallinity. The effect of γ-chloropropyltrimethoxysilane and maleic anhydride grafted polypropylene resin is to introduce highly active functional groups such as carboxyl and epoxy groups into it, which interact with each other to build a cross-linked structure, thereby increasing the regularity of the polypropylene molecular chain and restricting its free movement. In addition, the maleic anhydride grafted polypropylene resin can effectively improve the adhesion between the various components. When polypropylene interacts with the polyphenylene sulfide fiber loaded with modified nano-silica, it can more effectively transmit stress and synergistically resist external forces, thereby significantly improving the strength and deformation resistance of the material. The polyphenylene sulfide fiber loaded with modified nano-silica has a large contact area with the polypropylene molecular chain due to its small size and high specific surface area. When the two are combined, the polyphenylene sulfide The benzene rings and sulfide bonds in the fiber attract each other with the polypropylene molecular chains based on the intermolecular van der Waals forces and dipole-dipole interactions. The functional groups on the surface of nano-silica can chemically bond or physically adsorb with the active sites on the polypropylene molecular chains, enhancing the intermolecular interaction force and interface compatibility. This close combination builds a channel for the transmission of stress between the two materials. When external force acts on the composite material, the stress can be quickly and evenly transmitted between the polypropylene and polyphenylene sulfide fibers along the bridges formed by these chemical bonds, effectively avoiding the occurrence of stress concentration and local damage, thereby significantly improving the material's bearing capacity, enabling the material to better resist deformation and damage when subjected to external forces, further improving the material's strength, and optimizing the material's overall performance. DETAILED DESCRIPTION
[0024] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0025] Example 1
[0026] A method for preparing high-strength PP plastic, the preparation method of this embodiment comprises the following steps:
[0027] (1) mixing polyphenylene sulfide and N-methyl pyrrolidone, and stirring at room temperature for 8 hours to obtain a polyphenylene sulfide solution;
[0028] (2) After stirring the modified nano-silica and N-methylpyrrolidone for 1 hour, the modified nano-silica and N-methylpyrrolidone were added dropwise to the polyphenylene sulfide solution and stirred at variable speed to obtain a mixed solution;
[0029] (3) electrospinning the mixed solution, and drying it in vacuum at 70° C. for 10 h after spinning to obtain polyphenylene sulfide fibers loaded with modified nano-silica;
[0030] (4) Polypropylene, polyphenylene sulfide fiber loaded with modified nano-silica, calcium stearate, γ-chloropropyltrimethoxysilane, maleic anhydride grafted polypropylene resin and potassium persulfate are mixed, stirred at 50°C for 2 hours, melted in a twin-screw extruder, extruded and annealed to obtain a high-strength PP plastic.
[0031] The mass ratio of polyphenylene sulfide to N-methylpyrrolidone in step (1) of this embodiment is 0.8:15.
[0032] The mass ratio of modified nano-silica, N-methylpyrrolidone and polyphenylene sulfide solution in step (2) of this embodiment is 1.39:8:20;
[0033] The preparation method of the modified nano silicon dioxide of this embodiment is:
[0034] Nano-silica with an average particle size of 30 nm, anhydrous ethanol, methyltriethoxysilane, polyethylene glycol with a molecular weight of 2000 and potassium persulfate were ultrasonically mixed in a mass ratio of 1.1:15:0.08:0.15:0.01, stirred at 60°C for 3 hours, centrifuged, and filtered through a 200-mesh filter cloth. The resulting precipitate was washed with anhydrous ethanol and dried at 60°C for 12 hours to obtain modified nano-silica.
[0035] The parameters of the ultrasonic step of this embodiment are: ultrasonic frequency is 30kHz, ultrasonic temperature is 40°C, and ultrasonic time is 20min; the parameters of the centrifugal step of this embodiment are: centrifugal speed is 6000rmp, and centrifugal time is 10min.
[0036] The flow rate of the dropwise addition step in step (2) of this embodiment is 5 mL / min; the parameters of the variable speed stirring in step (2) of this embodiment are: the stirring temperature is 70°C, first stirring at 400 rpm for 1 hour, and then stirring at 1200 rpm for 20 minutes.
[0037] The parameters of the electrospinning step in step (3) of this embodiment are: voltage of 12 kV, distance between the nozzle and the receiving plate of 12 cm, flow rate of 0.3 mL / h, and stretch ratio of 8.
[0038] The mass ratio of polypropylene, polyphenylene sulfide fiber loaded with modified nano-silica, calcium stearate, γ-chloropropyltrimethoxysilane, maleic anhydride grafted polypropylene resin and potassium persulfate in step (4) of this embodiment is 5.2:1.12:0.28:0.3:0.6:0.02.
[0039] The parameters of the twin-screw extruder in step (4) of this embodiment are: extrusion temperature of 100°C, extrusion pressure of 14 MPa, and extrusion speed of 25 m / min; the parameters of the annealing step in step (4) of this embodiment are: annealing temperature of 100°C, and annealing time of 1.3 h.
[0040] Example 2
[0041] A method for preparing high-strength PP plastic, the preparation method of this embodiment comprises the following steps:
[0042] (1) mixing polyphenylene sulfide and N-methyl pyrrolidone, and stirring at room temperature for 12 hours to obtain a polyphenylene sulfide solution;
[0043] (2) After stirring the modified nano-silica and N-methylpyrrolidone for 2 hours, the modified nano-silica and N-methylpyrrolidone were added dropwise to the polyphenylene sulfide solution with variable speed stirring to obtain a mixed solution;
[0044] (3) electrospinning the mixed solution, and drying it in vacuum at 70° C. for 10 h after spinning to obtain polyphenylene sulfide fibers loaded with modified nano-silica;
[0045] (4) Polypropylene, polyphenylene sulfide fiber loaded with modified nano-silica, calcium stearate, γ-chloropropyltrimethoxysilane, maleic anhydride grafted polypropylene resin and potassium persulfate are mixed, stirred at 70°C for 3 hours, melted in a twin-screw extruder, extruded and annealed to obtain a high-strength PP plastic.
[0046] The mass ratio of polyphenylene sulfide to N-methylpyrrolidone in step (1) of this embodiment is 1.2:25.
[0047] The mass ratio of modified nano-silica, N-methylpyrrolidone and polyphenylene sulfide solution in step (2) of this embodiment is 1.73:12:30;
[0048] The preparation method of the modified nano silicon dioxide of this embodiment is:
[0049] Nano-silica with an average particle size of 70 nm, anhydrous ethanol, methyltriethoxysilane, polyethylene glycol with a molecular weight of 2000 and potassium persulfate were ultrasonically mixed in a mass ratio of 2.5:25:0.12:0.25:0.03, stirred at 100°C for 5 hours, centrifuged, and filtered through a 200-mesh filter cloth. The resulting precipitate was washed with anhydrous ethanol and dried at 60°C for 12 hours to obtain modified nano-silica.
[0050] The parameters of the ultrasonic step of this embodiment are: ultrasonic frequency is 50kHz, ultrasonic temperature is 60°C, and ultrasonic time is 40min; the parameters of the centrifugal step of this embodiment are: centrifugal speed is 10000rmp, and centrifugal time is 20min.
[0051] The flow rate of the dropwise addition step in step (2) of this embodiment is 5 mL / min; the parameters of the variable speed stirring in step (2) of this embodiment are: the stirring temperature is 90°C, first stirring at a speed of 600 rpm for 1-3 hours, and then stirring at a speed of 1800 rpm for 40 minutes.
[0052] The parameters of the electrospinning step in step (3) of this embodiment are: voltage of 20 kV, distance between the nozzle and the receiving plate of 18 cm, flow rate of 0.7 mL / h, and stretch ratio of 12.
[0053] The mass ratio of polypropylene, polyphenylene sulfide fiber loaded with modified nano-silica, calcium stearate, γ-chloropropyltrimethoxysilane, maleic anhydride grafted polypropylene resin and potassium persulfate in step (4) of this embodiment is 7:1.3:0.46:0.7:1:0.04.
[0054] The parameters of the twin-screw extruder in step (4) of this embodiment are: extrusion temperature of 140°C, extrusion pressure of 18 MPa, and extrusion speed of 35 m / min; the parameters of the annealing step in step (4) of this embodiment are: annealing temperature of 110°C, and annealing time of 1.5 h.
[0055] Example 3
[0056] A method for preparing high-strength PP plastic, the preparation method of this embodiment comprises the following steps:
[0057] (1) mixing polyphenylene sulfide and N-methyl pyrrolidone, and stirring at room temperature for 10 hours to obtain a polyphenylene sulfide solution;
[0058] (2) After stirring the modified nano-silica and N-methylpyrrolidone for 1.5 hours, the mixture was added dropwise to the polyphenylene sulfide solution and stirred at variable speed to obtain a mixed solution;
[0059] (3) electrospinning the mixed solution, and drying it in vacuum at 70° C. for 10 h after spinning to obtain polyphenylene sulfide fibers loaded with modified nano-silica;
[0060] (4) Polypropylene, polyphenylene sulfide fiber loaded with modified nano-silica, calcium stearate, γ-chloropropyltrimethoxysilane, maleic anhydride grafted polypropylene resin and potassium persulfate are mixed, stirred at 60°C for 2.5 hours, melted in a twin-screw extruder, extruded and annealed to obtain a high-strength PP plastic.
[0061] The mass ratio of polyphenylene sulfide to N-methylpyrrolidone in step (1) of this embodiment is 1:20.
[0062] The mass ratio of modified nano-silica, N-methylpyrrolidone and polyphenylene sulfide solution in step (2) of this embodiment is 1.56:10:25;
[0063] The preparation method of the modified nano silicon dioxide of this embodiment is:
[0064] Nano-silica with an average particle size of 50 nm, anhydrous ethanol, methyltriethoxysilane, polyethylene glycol with a molecular weight of 2000 and potassium persulfate were ultrasonically mixed in a mass ratio of 1.8:20:0.1:0.2:0.02, stirred at 80°C for 4 hours, centrifuged, and filtered through a 200-mesh filter cloth. The resulting precipitate was washed with anhydrous ethanol and dried at 60°C for 12 hours to obtain modified nano-silica.
[0065] The parameters of the ultrasonic step of this embodiment are: ultrasonic frequency is 40kHz, ultrasonic temperature is 50°C, and ultrasonic time is 30min; the parameters of the centrifugal step of this embodiment are: centrifugal speed is 8000rmp, and centrifugal time is 15min.
[0066] The flow rate of the dropwise addition step in step (2) of this embodiment is 5 mL / min; the parameters of the variable speed stirring in step (2) of this embodiment are: the stirring temperature is 80°C, first stirring at a speed of 500 rpm for 1-3 hours, and then stirring at a speed of 1500 rpm for 30 minutes.
[0067] The parameters of the electrospinning step in step (3) of this embodiment are: voltage of 16 kV, distance between the nozzle and the receiving plate of 15 cm, flow rate of 0.5 mL / h, and stretch ratio of 10.
[0068] The mass ratio of polypropylene, polyphenylene sulfide fiber loaded with modified nano-silica, calcium stearate, γ-chloropropyltrimethoxysilane, maleic anhydride grafted polypropylene resin and potassium persulfate in step (4) of this embodiment is 6.1:1.21:0.37:0.5:0.8:0.03.
[0069] The parameters of the twin-screw extruder in step (4) of this embodiment are: extrusion temperature of 120°C, extrusion pressure of 16 MPa, and extrusion speed of 30 m / min; the parameters of the annealing step in step (4) of this embodiment are: annealing temperature of 105°C, and annealing time of 1.4 h.
[0070] Comparative Example 1
[0071] On the basis of Example 3, the modified nano-silicon dioxide was removed and replaced with an equal weight of nano-silicon dioxide, and the other conditions were consistent with Example 3.
[0072] Comparative Example 2
[0073] On the basis of Example 3, methyltriethoxysilane was removed and replaced with an equal weight of anhydrous ethanol, and other conditions were consistent with Example 3.
[0074] Comparative Example 3
[0075] On the basis of Example 3, polyethylene glycol with a molecular weight of 2000 was removed and replaced with an equal weight of anhydrous ethanol. Other conditions were the same as those in Example 3.
[0076] Comparative Example 4
[0077] On the basis of Example 3, the electrospinning step was removed, and other conditions were consistent with Example 3.
[0078] Comparative Example 5
[0079] On the basis of Example 3, γ-chloropropyltrimethoxysilane was removed and replaced with an equal weight of maleic anhydride grafted polypropylene resin, and other conditions were consistent with Example 3.
[0080] Comparative Example 6
[0081] On the basis of Example 3, the maleic anhydride grafted polypropylene resin was removed and replaced with an equal weight of γ-chloropropyltrimethoxysilane. Other conditions were the same as those in Example 3.
[0082] The PP plastics prepared in Examples 1-3 and Comparative Examples 1-6 are used as samples:
[0083] After making a 100*10*5mm V-shaped notch with a depth of 2mm, the flexural modulus (MPa), impact strength (kJ / m 2 ) and surface hardness (HV);
[0084] After making a dumbbell-shaped standard specimen of 150 mm × 10 mm × 4 mm, the tensile speed was set to 50 mm / min, and the tensile strength (MPa) of the specimen was tested according to ASTM D638;
[0085] The average value of the test results is recorded in Table 1.
[0086] Table 1
[0087]
[0088] As shown in Table 1, the impact strength and surface hardness of the PP plastics prepared by Examples 1-3 are significantly higher than those of the PP plastics prepared by Comparative Examples 1-6, and the flexural modulus, tensile strength and other properties are also better than those of Comparative Examples 1-6, indicating that the modified nano-silicon dioxide is loaded on the polyphenylene sulfide fiber in the present invention, and the modified nano-silicon dioxide can be better interpenetrated and integrated into the polymer molecular chain, thereby enhancing the binding force between the polyphenylene sulfide molecules, limiting the free slip and movement of the molecular chain, thereby effectively improving the strength and toughness of the material, and avoiding the premature destruction of the material caused by stress concentration; and the polypropylene molecular chain, under the joint action of components such as γ-chloropropyltrimethoxysilane and maleic anhydride grafted polypropylene resin, enhances the cross-linking structure between the molecular chains through chemical bonding and physical entanglement, thereby enhancing the interface compatibility and stress transfer efficiency, so that the stress can be quickly and evenly transferred between the polypropylene and the polyphenylene sulfide fiber along the bridge formed by these chemical bonds, significantly improving the strength of the material and optimizing the overall performance of the material. The components of the present invention complement each other and synergistically exert beneficial effects, and any modification or alteration of any component or preparation step thereof cannot achieve the above effects.
[0089] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing high-strength PP plastic, characterized in that: The preparation method comprises the following steps: (1) Mix polyphenylene sulfide and N-methylpyrrolidone, and stir at room temperature for 8-12 hours to obtain a polyphenylene sulfide solution; (2) After stirring the modified nano-silica and N-methylpyrrolidone for 1-2 hours, the modified nano-silica and N-methylpyrrolidone are added dropwise to the polyphenylene sulfide solution and stirred at variable speed to obtain a mixed solution; (3) electrospinning the mixed solution, and then drying it in vacuum at 70°C for 10 h to obtain polyphenylene sulfide fibers loaded with modified nano-silica; (4) Mixing polypropylene, polyphenylene sulfide fiber loaded with modified nano-silica, calcium stearate, γ-chloropropyltrimethoxysilane, maleic anhydride grafted polypropylene resin and potassium persulfate, stirring at 50-70°C for 2-3h, then melting in a twin-screw extruder, extruding and annealing to obtain a high-strength PP plastic; In step (2), the mass ratio of the modified nano-silica, N-methylpyrrolidone and polyphenylene sulfide solution is 1.39-1.73:8-12:20-30; The preparation method of the modified nano silicon dioxide is: Nano-silica with an average particle size of 30-70 nm, anhydrous ethanol, methyltriethoxysilane, polyethylene glycol with a molecular weight of 2000 and potassium persulfate are ultrasonically mixed in a mass ratio of 1.1-2.5:15-25:0.08-0.12:0.15-0.25:0.01-0.03, stirred at 60-100° C. for 3-5 hours, centrifuged, filtered through a 200-mesh filter cloth, and the resulting precipitate is washed with anhydrous ethanol and dried at 60° C. for 12 hours to obtain modified nano-silica.
2. The method for preparing a high-strength PP plastic according to claim 1, characterized in that: The mass ratio of polyphenylene sulfide to N-methylpyrrolidone in step (1) is 0.8-1.2:15-25.
3. The method for preparing a high-strength PP plastic according to claim 1, characterized in that: The parameters of the ultrasonic step are: ultrasonic frequency of 30-50kHz, ultrasonic temperature of 40-60°C, and ultrasonic time of 20-40min; the parameters of the centrifugal step are: centrifugal speed of 6000-10000rmp, and centrifugal time of 10-20min.
4. The method for preparing a high-strength PP plastic according to claim 1, characterized in that: The flow rate of the dropwise addition step in step (2) is 5 mL / min; the parameters of the variable speed stirring are: the stirring temperature is 70-90°C, the stirring speed is first 400-600 rpm for 1-3 hours, and then the stirring speed is 1200-1800 rpm for 20-40 minutes.
5. The method for preparing a high-strength PP plastic according to claim 1, characterized in that: The parameters of the electrospinning step in step (3) are: voltage of 12-20 kV, distance between the nozzle and the receiving plate of 12-18 cm, flow rate of 0.3-0.7 mL / h, and stretch ratio of 8-12.
6. The method for preparing a high-strength PP plastic according to claim 1, characterized in that: In step (4), the mass ratio of the polypropylene, the polyphenylene sulfide fiber loaded with modified nano-silica, the calcium stearate, the γ-chloropropyltrimethoxysilane, the maleic anhydride grafted polypropylene resin and the potassium persulfate is 5.2-7:1.12-1.3:0.28-0.46:0.3-0.7:0.6-1:0.02-0.
04.
7. The method for preparing a high-strength PP plastic according to claim 1, characterized in that: The parameters of the twin-screw extruder in step (4) are: extrusion temperature of 100-140°C, extrusion pressure of 14-18 MPa, and extrusion speed of 25-35 m / min; the parameters of the annealing step are: annealing temperature of 100-110°C, and annealing time of 1.3-1.5 h.
Citation Information
Patent Citations
Antioxidation polyphenylene sulfide / modified nano silicon dioxide composite fiber and preparation method thereof
CN110205703A
Fiber glass enhanced polypropylene material with high ageing ressistance of anti heat and oxygen
CN1696187A